An Electrocatalyst for a Hydrogen Evolution Reaction in an Alkaline Medium: Three‐Dimensional Graphene Supported CeO2 Hollow Microspheres. Issue 35 (26th August 2018) - Liu, Miaomiao; Ji, Zhenyuan; Shen, Xiaoping; Zhou, Hu; Zhu, Jun; Xie, Xulan; Song, Chunsen; Miao, Xuli; Kong, Lirong; Zhu, Guoxing
Abstract : Transition metal oxides (TMO) are promising candidates for low‐cost and high‐efficiency catalysts for the hydrogen evolution reaction (HER). However, the low conductivity and severe agglomeration of catalyst particles hinder their practical application. Herein, we report an effective HER electrocatalyst of 3D‐rGO‐CeO2 with three‐dimensional reduced graphene oxide (3D‐rGO) decorated with CeO2 hollow microspheres through a hydrothermal self‐assembly approach. It is shown that the CeO2 hollow microspheres with an average size of ca. 680 nm are uniformly encapsulated within the porous structure of 3D‐rGO. Compared with bare CeO2 hollow microspheres, the 3D‐rGO‐CeO2 composite exhibits remarkably enhanced electrocatalytic activity for HER with a relatively low onset overpotential of 192 mV, a smaller overpotential of 0.34 V at the current density of 10 mA cm –2, and a modest Tafel slope of 112.8 mV decade –1 in a 1m KOH solution. The enhanced performance of 3D‐rGO‐CeO2 can be ascribed to the introduction of 3D rGO in the composite, which provides a highly conductive network for rapid charge‐carrier transmission, and rich porous structures for the easy access of the electrolyte to the catalyst during the HER process. Abstract : The 3D‐rGO‐CeO2 composite based on three‐dimensional rGO and CeO2 hollow microspheres was successfully synthesized by a hydrothermal self‐assembly approach, which showed an enhanced electrocatalytic performance for a hydrogen evolution reaction in an alkaline medium.